2018
DOI: 10.3168/jds.2018-14510
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of daily activity patterns and biomarkers of pain, inflammation, and stress in lactating dairy cows diagnosed with clinical metritis

Abstract: The objectives of the present case-control study were to assess (1) daily activity patterns (lying time, number of steps, number of lying bouts, and lying bout duration), and (2) circulating concentrations of biomarkers of pain (substance P), inflammation (haptoglobin), and stress (cortisol) in lactating dairy cows diagnosed with clinical metritis. Lactating dairy cows (n = 200) from 2 commercial dairy herds were enrolled in the present study. Cows diagnosed with clinical metritis (n = 100) at 7 ± 3 d in milk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 50 publications
2
65
1
9
Order By: Relevance
“…Regardless of health status, primiparous cows experience a greater inflammatory response than multiparous cows during the early postpartum (Humblet et al, 2006). In addition, previous research showed that primiparous cows experiencing metritis have increased lying time compared with nondiseased cows, but no differences were observed in multiparous cows, suggesting more expression of the sickness behavior in primiparous cows (Barragan et al, 2018). It is possible that primiparous cows have an exacerbated inflammatory response shortly after calving due to their first contact with antigens and, as they mature, they develop a more efficient immune response.…”
Section: Discussionmentioning
confidence: 95%
“…Regardless of health status, primiparous cows experience a greater inflammatory response than multiparous cows during the early postpartum (Humblet et al, 2006). In addition, previous research showed that primiparous cows experiencing metritis have increased lying time compared with nondiseased cows, but no differences were observed in multiparous cows, suggesting more expression of the sickness behavior in primiparous cows (Barragan et al, 2018). It is possible that primiparous cows have an exacerbated inflammatory response shortly after calving due to their first contact with antigens and, as they mature, they develop a more efficient immune response.…”
Section: Discussionmentioning
confidence: 95%
“…Assessment of daily activity patterns showed that cows in the HFM group were less active and spent more time lying down than those cows in the LFM group following calving. Although no specific information studying the role of prepartum NEFA concentration on postpartum behavior is currently available, some evidence indicates that behavior is modified in animals that suffer from disorders or diseases causing stress and pain [57][58][59][60]. As previously mentioned, the incidence of disease did not differ between groups, which could confirm that fat mobilization plays an important role influencing daily activity during the postpartum, regardless of the presence of disease.…”
Section: Discussionmentioning
confidence: 64%
“…In turn, LPS inhibits the release of GnRH and LH and aromatase activity within ovarian follicles, resulting in decreased follicular growth and decreased blood estradiol Herath et al, 2009). Moreover, cows diagnosed with infectious diseases (e.g., metritis) early in lactation typically have increased serum concentrations of haptoglobin compared with nondiseased cows (Stangaferro et al, 2016a,b,c;Barragan et al, 2018). Dubuc et al (2012) showed that cycling lactating cows at 21 DIM had reduced serum concentrations of haptoglobin for the first 3 wk after calving compared with anovular cows at 21,35,49,or 63 DIM. Regardless of parity, ND lactating cows produced more milk at first DHIA test than KET+ cows.…”
Section: Discussionmentioning
confidence: 99%